CREATIVE TEACHING - REFLECTIONS AND APPROACHES - Sofia Loredana TUDOR (Universitaria Publishing House, Craiova, 2024)
In modern pedagogy, the concept of teaching has acquired a lot of new meanings and has had numerous interpretations, but also reinterpretations. The redefinition of teaching is imposed by the transition process from "transmission pedagogy" to "active and constructive pedagogy", oriented in the direction of effective learning, immediately, but also in the medium and long term. Thus, the relationship between teaching and learning becomes very important, as actions subordinate to the training activity. In postmodern (contemporary) pedagogy, the concept of teaching is defined as the action of formative communication of the pedagogical/didactic message, designed according to the objectives of the training activity, carried out at the level of the common repertoire between the teacher and the class of students, aimed at immediate learning and in the medium and long term, regulated and self-regulated by continuous evaluation of results. Teaching is the dominant activity of the teacher and a causal variable on which the state of preparation of the students largely depends. Approaching the creative dimension in teaching is considered an optimal way for the development of the student's personality, in the context of contemporary educational models, which emphasize educational innovation.